Solid Lipid Nanoparticles as an Efficient Delivery System for Natural Skin Care Cosmetics: A Review - Omolbanin Shahraki; Sara Daneshmand (Research in Molecular Medicine)
Background: Natural skin care products, as health & beauty products, have formulations derived from natural active ingredients. Cosmetic actives have been incorporated into their novel formulations such as sunscreens and anti-aging products, but the challenges associated with their low solubility, low penetration, and physicochemical instability upon dermal application remain unresolved. To overcome these limitations, one method is to use lipid-based carriers, which have been recognized for their crucial role in enhancing their low solubility, increasing skin permeation, and enhancing steadiness. This review study focuses on current advancements in skin care formulations that employ a new nanotechnology-based system consisting of solid lipid nanoparticles (SLNs).